1038 Comparative assessment of phasic left atrial and regional left ventricular strain in patients with cardiac amyloidosis and LV hypertrophy. (17th January 2020) - Brand, A M; Baldenhofer, G; Frumkin, D; Huebscher, A; Stangl, K; Knebel, F
Abstract: Background: Echocardiographic hallmarks of cardiac amyloidosis (CA), such as increased wall thickness of the LV and sparkling appearance of the myocardium, are limited by a reduced diagnostic accuracy. Purpose: We sought to evaluate the diagnostic value of phasic left atrial strain alterations and of regional global longitudinal systolic LV strain (LVGLS) reductions in patients with CA and with other forms of LV hypertrophy. Methods: Standard apical 4-chamber views were stored for offline analysis (Vivid E9, GE, Vingmed, Horton) in 54 patients who underwent endomyocardial biopsy for unclear LV hypertrophy. We then analyzed LVGLS as well as LA reservoir, conduit, and contraction strain using 2D speckle tracking echocardiography (2DSTE; EchoPAC software, GE). To assess regional LVGLS, the average of apical strain values / (average of mid + basal LV strain values) was calculated (relative apical sparing; RELAPS). Receiver operating characteristic (ROC) curve analyses and a multivariate logistic regression analysis were performed to investigate the diagnostic value of the respective LA and LV deformation analysis. Results: CA was bioptically confirmed in 34 patients (13 TTR, 1 AA, 20 AL amyloidosis). In 18 patients, myocardial biopsy revealed other forms of LV hypertrophy, such as hypertensive heart disease (n = 2), hypertrophic cardiomyopathy (n = 12), and inflammatory myocardial diseases (n = 4). Mean septal wall thickness (17.7 ± 2.9 mm and 17.9 ± 4.3 mm) and left atrial volume index (43.8 ± 12.2 and 44.1 ± 17.2) were not different between groups. RELAPS was significantly higher in patients with CA (1.37 ± 0.94 vs. 0.86 ± 0.29, p<.007). Phasic atrial mechanics were significantly worse in CA (LA reservoir, conduit, and contraction strain 10.0 ± 5.2%, -6.5 ± 3.5%, and -5.0 ± 4.1%, respectively, in CA; and 22.7 ± 7.8%, -13.9 ± 5.2%, and -13.0 ± 5.5%, in LVH, respectively; p<.001). With an area under the curve (AUC) of 0.91, and a sensitivity and specificity of 91.2 and 84.2% for a cut-off value of <15.8%, LA reservoir strain showed a higher diagnostic accuracy in discriminating CA from LVH than the parameter RELPAS (AUC 0.74, sensitivity and specificity 60% and 71% for a cut-off of >1.0; p<.05). LA conduit and contraction strain performed significantly better than RELAPS as well (AUC 0.87 for conduit, and AUC 0.86 for contraction function; p<.001 each). Of all echocardiographic parameters, LA reservoir strain remained significantly associated with CA in a multivariate regression model. Conclusions: LA strain during all three phases of the atrial cycle was significantly reduced in patients with CA compared to other forms of LVH, and showed a markedly higher diagnostic accuracy than regional LV strain analysis, with LA reservoir strain showing highest discriminative value. The assessment of LA strain, as part of a comprehensive echocardiographic assessment, may be useful to rule-in the possible diagnosis of CA in patients with unclear LV hypertrophy.